Evaluasi Kebijakan Stabilisasi Harga Pangan Pada Kemampuan Belanja Konsumen (Studi Kasus Pasar Raya MMTC Medan) - Riski Halomoan Siregar; Dede Ruslan (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study aims to evaluate the effect of food price control policies on people's purchasing power at Pasar Raya MMTC Medan. Traditional markets have a strategic role in the local economy as a center for basic needs transactions. However, fluctuations in food prices often create uncertainty that impacts people's purchasing power. This study uses a qualitative approach by collecting data through interviews with five sellers and five buyers in traditional markets. The results of the analysis show that food price control policies have a positive effect on price stability, which directly increases people's purchasing power. Sellers feel helped by stable prices, because it makes it easier to plan their businesses, although profit margins have decreased slightly. On the other hand, consumers enjoy more affordable food prices, although in some cases there is a decrease in product quality and uncertainty about the availability of goods. In addition, the findings of this study reveal that food price control policies are in line with Islamic economic principles that prioritize justice and social welfare. Overall, this policy shows quite good results in creating price stability and increasing consumer satisfaction. However, the effectiveness of the policy can be improved by improving implementation in the field and balancing the interests of consumers and business actors. The government is expected to continue to monitor and evaluate this policy, while considering input from various parties to improve the effectiveness of food price control in the future.